2002
DOI: 10.2337/diacare.25.5.809
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Evaluation of Staging Dietary Patterns to Reduce the Risk of Diabetes in African-American Women

Abstract: OBJECTIVE -This study evaluated the 3-month follow-up data of the Eat Well, Live Well Nutrition Program, a culturally specific, peer-led dietary change program designed to reduce the risk of type 2 diabetes in low-income African-American women. This peer-led program was delivered in the community and was tailored to the participants' stage of change for individual dietary patterns. We report the results of the 3-month intervention and the extent to which dietary changes and other key outcomes were maintained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
85
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 18 publications
0
85
0
Order By: Relevance
“…9 Applications of the model have been documented in predominantly African American communities for smoking cessation, [10][11][12] exercise, [13][14][15] and dietary behavior change. [16][17][18] The health locus of control model defi nes an individual' s sense of control over his or her health as being directly related to his or her own beliefs and actions (internal) or the result of external factors, such as of fate or chance (chance) or the infl uence of other important persons (powerful others). 19 The model is based on social learning theory, and there is evidence that a person' s locus of control is associated with health behavior, particularly in combination with other predictive factors.…”
mentioning
confidence: 99%
“…9 Applications of the model have been documented in predominantly African American communities for smoking cessation, [10][11][12] exercise, [13][14][15] and dietary behavior change. [16][17][18] The health locus of control model defi nes an individual' s sense of control over his or her health as being directly related to his or her own beliefs and actions (internal) or the result of external factors, such as of fate or chance (chance) or the infl uence of other important persons (powerful others). 19 The model is based on social learning theory, and there is evidence that a person' s locus of control is associated with health behavior, particularly in combination with other predictive factors.…”
mentioning
confidence: 99%
“…The 1.4 daily F+V serving increase observed in the FCF results compares favorably with the 0.7-1.4 F+V serving increases observed in the church-based Body and Soul intervention, (Resnicow, Campbell et al 2004) with the 1.0-1.4 F+V serving increases in the Eat for Life intervention (Resnicow, Jackson et al 2001) and with those in the Women's Health Trial Feasibility Study in Minority Populations. (Bhargava and Hays 2004) The 3% decrease in calories from fat compared with baseline is also similar to the 4% reduction observed among the younger, but heavier and lower socioeconomic status African-American women in the Eat Well, Live Well Nutrition Program in the Midwest, (Auslander, Haire-Joshu et al 2002) though the FCF participants baseline levels were somewhat higher (38% vs. 36%). Actually, the nearly identical saturated (11-13%) and total dietary fat intakes reported for both of these similarly sized (394 vs. 364), but sociodemographically different (region of residence as well as age, SES and severity of obesity) samples of African-American women are striking.…”
Section: Discussionmentioning
confidence: 52%
“…2000) More recent lifestyle intervention studies in non-clinical samples that included a substantial proportion of African Americans include: e.g., the Diabetes Prevention Program, (Knowler, Barrett-Connor et al 2002) Body and Soul, (Resnicow, Campbell et al 2004) the Women's Health Trial, (Bhargava and Hays 2004) the PREMIER study, (Appel, Champagne et al 2003) the Women's Health Initiative, (2004) and the Eat Well, Live Well Nutrition Program in the Midwest. (Auslander, Haire-Joshu et al 2002) However, none could be identified that specifically targeted the needs of middle aged and older, healthy, obese African-American women, a high-risk group that historically has been observed to have greater adherence challenges and poorer outcomes. (Kumanyika 2002(Kumanyika , 2004 The African-American Women Fight Cancer with Fitness (FCF) study tested the efficacy of a culturally-targeted nutrition and physical activity intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Community researchers have concluded that focus groups are a successful way to identify barriers to public health initiatives. 46 Additionally, previous research shows that direct and indirect recruitment strategies among African American women are a beneficial means to attract and maintain interest among research participants. 47 For this study, 23 research participants were recruited and signed consent forms, 14 participants were included in the pre and post test analysis and 13 were included in the one month follow up analysis.…”
Section: Discussionmentioning
confidence: 99%